Observer Design for Distributed Network Systems with Communication Delays ⁎. Issue 33 (2018) - Adachi, Ryosuke; Yamashita, Yuh; Kobayashi, Koichi
Abstract: In this paper, we consider the design problem of an unknown-input observer for distributed network systems under existence of communication delays. It is assumed that an input of each node in a network is calculated from the estimate of own node. Instead of the unknown inputs, each node calculates alternative ones from own estimate and utilizes these values in the calculation of the estimation and the delay compensation. The stability of the estimation error of the proposed observer is proven by a Lyapunov-Krasovskii functional. The stability condition is given by a linear matrix inequality (LMI). Finally, a result of a numerical simulation is shown to verify the effectiveness of the proposed method.